Too large to fit? Recent developments in macromolecular imprinting. - Ge, Yi; Turner, Anthony P. F. (Elsevier Science B.V., Amsterdam., 2008)
Molecular imprinting involves the synthesis of polymers in the presence of a template to produce complementary binding sites with specific recognition ability. The technique has been successfully applied as a measurement and separation technology, producing a uniquely robust and antibody-like polymeric material. Low molecular weight molecules have been extensively exploited as imprint templates, leading to significant achievements in solid-phase extraction, sensing and enzyme-like catalysis. By contrast, macromolecular imprinting remains underdeveloped, principally because of the lack of binding site accessibility. In this review, we focus on the most recent developments in this area, not only covering the widespread use of biological macro-templates but also highlighting the emerging use of synthetic macro-templates, such as dendrimers and hyperbranched polymers.